Cognitive Profiles in Parkinson's Disease and Their Relation to Dementia: A Data-Driven Approach. (18th October 2012) - Liepelt-Scarfone, Inga; Gräber, Susanne; Fruhmann Berger, Monika; Feseker, Anne; Baysal, Gülsüm; Csoti, Ilona; Godau, Jana; Gaenslen, Alexandra; Huber, Heiko; Srulijes, Karin; Brockmann, Kathrin; Berg, Daniela
Abstract : Parkinson's disease is characterized by a substantial cognitive heterogeneity, which is apparent in different profiles and levels of severity. To date, a distinct clinical profile for patients with a potential risk of developing dementia still has to be identified. We introduce a data-driven approach to detect different cognitive profiles and stages. Comprehensive neuropsychological data sets from a cohort of 121 Parkinson's disease patients with and without dementia were explored by a factor analysis to characterize different cognitive domains. Based on the factor scores that represent individual performance in each domain, hierarchical cluster analyses determined whether subgroups of Parkinson's disease patients show varying cognitive profiles. A six-factor solution accounting for 65.2% of total variance fitted best to our data and revealed high internal consistencies (Cronbach's alpha coefficients > 0.6 ). The cluster analyses suggested two independent patient clusters with different cognitive profiles. They differed only in severity of cognitive impairment and self-reported limitation of activities of daily living function but not in motor performance, disease duration, or dopaminergic medication. Based on a data-driven approach, divers cognitive profiles were identified, which separated early and more advanced stages of cognitive impairment in Parkinson's disease without dementia. Importantly, these profiles were independent of motor progression.